Diffusion tensor imaging in children with unilateral hearing loss: a pilot study - Rachakonda, Tara; Shimony, Joshua S.; Coalson, Rebecca S.; Lieu, Judith E. C. (Frontiers in Systems Neuroscience, 2014)
Objective: Language acquisition was assumed to proceed normally in children with unilateral hearing loss (UHL) since they have one functioning ear. However, children with UHL score poorly on speech-language tests and have higher rates of educational problems compared to normal hearing (NH) peers. Diffusion tensor imaging (DTI) is an imaging modality used to measure microstructural integrity of brain white matter. The purpose of this pilot study was to investigate differences in fractional anisotropy (FA) and mean diffusivity (MD) in hearing- and non-hearing-related structures in the brain between children with UHL and their NH siblings. Study Design: Prospective observational cohort Setting: Academic medical center. Subjects and Methods: 61 children were recruited, tested and imaged. 29 children with severe-to-profound UHL were compared to 20 siblings with NH using IQ and oral language testing, and MRI with DTI. 12 children had inadequate MRI data. Parents provided demographic data and indicated whether children had a need for an individualized educational program (IEP) or speech therapy (ST). DTI parameters were measured in auditory and non-auditory regions of interest (ROIs). Between-group comparisons were evaluated with non-parametric tests. Results: Lower FA of left lateral lemniscus was observed for children with UHL compared to their NH siblings, as well as trends towards differences in other auditory and nonauditory regions. Correlation analyses showed associations between several DTI parameters and outcomes in children with UHL. Regression analyses revealed relationships between educational outcome variables and several DTI parameters, which may provide clinically useful information for guidance of speech therapy. Discussion/Conclusion: White matter microstructural patterns in several brain regions are preserved despite unilateral rather than bilateral auditory input which contrasts with findings in patients with bilateral hearing loss.